2022
DOI: 10.1108/jmtm-06-2021-0215
|View full text |Cite
|
Sign up to set email alerts
|

Buyer-supplier dyad on performance and sustainability

Abstract: PurposeThis paper investigates how the configuration of a supplier’s sustainable operations practices (SOPs) with a high sustainable performance affects a buyer’s organizational performance in the buyer-supplier dyad.Design/methodology/approachThis study first identifies the key SOPs using bibliometric and content analyses. Then, the research hypotheses are proposed using complexity theory and the resource-based view. This study applies fuzzy-set qualitative comparative analysis (fsQCA) on a sample of 74 buyer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…Whatever the relationship type between buyers and suppliers, buyers' support is necessary to implement and sustain lean in garment supplier factories (Hoque et al, 2020). Hao et al (2022) identified lean production as one of the significant sustainable operations practices and buyers can help their suppliers to enhance their sustainable operations practices, such as lean production and others, although they can select the suppliers who have implemented various high-level sustainable operations practices. It is "buyer-seller relationship" that plays an important role in determining buyers' intervention to assist suppliers in lean implementation (Hoque, 2021a(Hoque, , 2021b.…”
Section: Buyer-supplier Relational Dynamics To Mitigate Lean Challeng...mentioning
confidence: 99%
“…Whatever the relationship type between buyers and suppliers, buyers' support is necessary to implement and sustain lean in garment supplier factories (Hoque et al, 2020). Hao et al (2022) identified lean production as one of the significant sustainable operations practices and buyers can help their suppliers to enhance their sustainable operations practices, such as lean production and others, although they can select the suppliers who have implemented various high-level sustainable operations practices. It is "buyer-seller relationship" that plays an important role in determining buyers' intervention to assist suppliers in lean implementation (Hoque, 2021a(Hoque, , 2021b.…”
Section: Buyer-supplier Relational Dynamics To Mitigate Lean Challeng...mentioning
confidence: 99%
“…Theoretically, the research was based on RBV theory, which states that a business needs different resources to begin and expand its operation. These resources could be financial, physical, human resources, technological resources, reputation, and organizational resources to contribute towards the sustainable performance of the firm [25,118,119]. As such, the operation and performance evaluation roles of ISO 14001 and green servitization form the resource capacity of the firm to control their environmental management system [120].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Currently, negative environmental effects of energy and emissions, as well as air and water pollution from manufacturing firms, are no doubt affecting the overall sustainable performance [24,25]. As such, various governmental and non-governmental organizations are coming up with different campaigns for green production processes vis a vis sanctions to curb current and future environmental problems, while shareholders are considering investing in manufacturing firms that are conscious of green production practices to reduce global warming and other environmental problems, which will eventually increase sustainability performance [26][27][28].…”
Section: Introductionmentioning
confidence: 99%